Diseño del manual de procesos para la lubricadora Víctor Hugo en la ciudad de Babahoyo - Campuzano Obando, Milton Adolfo (2023)
This Degree Project refers to the administration of the Victor Hugo lubricator. It has been in the market for 10 years and has 4 workers and its owner administrator. Within the business, shortcomings were detected in the internal administrative and operational processes. So it was concluded that the company must have a Process Manual to improve internal management. The problems that were evidenced in the investigation were duplication of tasks, delay in the processes of the administrative area, inefficient process of approval of credit to customers, which causes a low performance of internal control......